TEACHING MATERIALS AND EQUIPMENT OF CROATIAN LANGUAGE LECTURE IN THE LANGUAGE AND SCRIPT OF HUNGARIAN NATIONAL MINORITIES - Tina Z. Varga Oswald; Marko D. Ek (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2011)
Bilingualism, as a social category within the educational system, requires special attention of professionals. Education in the language and script of national minorities is a part of an overall educational system. Pupils belonging to Hungarian minority in Croatia speak two languages, which they do not master equally, and are therefore considered as a challenge group to a teacher who teaches Croatian language opposite to native Hungarian language. There are several types of teaching activities that can be used for preparation of Croatian language lecture units for Hungarian minority pupils. These refer to teaching aids (teaching materials and equipment), which contribute to successful learning of foreign language and overcoming of linguistic obstacles. This paper presents a possible methodological approach to interpretation of the Dragutin Tadijanović's lyric Dugo u noć, u zimsku bijelu noć, which is taught to pupils in the 7th elementary grade, according to the plan and teaching program for the Croatian language teaching.